ANALISIS PENGARUH E-MONEY DAN BI7DRR TERHADAP JUMLAH UANG BEREDAR DENGAN INFLASI SEBAGAI MODERASI - Nabila, Farah; Munawar Ismail (Contemporary Studies in Economic, Finance and Banking, 2024)
The purpose of this study is to understand the influence of e-money transaction volume and the BI7DRR on the money supply in Indonesia, using inflation as a moderating variable. The data utilized consists of time series data from January 2020 to December 2022. The research employs multiple linear regression analysis techniques, including Moderating Regressions Analysis (MRA). Based on the research findings, it is revealed that both e-money transaction volume and the BI7DRR have a significant impact on the money supply (M1) in Indonesia. Furthermore, inflation act as a moderating predictor in the interavtion relationship between e-money transaction volume and the BI7DRR on the money supply in Indonesia.